Validation of a robust strategy for proton spot scanning for oesophageal cancer in the presence of anatomical changes - Møller, Ditte Sloth; Alber, Markus; Nordsmark, Marianne; Nyeng, Tine Bisballe; Lutz, Christina Maria; Hoffmann, Lone (Radiotherapy and oncology, 2019)
SFUD strategies with one or two posterior proton beams and three target coverage strategies are compared with IMRT and tested for robustness towards anatomical changes by recalculation on surveillance CTs during treatment. We find posterior beam SFUD combining PTV coverage with robust optimization increases robustness towards anatomical changes compared to IMRT.